PENGARUH INDEPENDENSI AUDITOR DAN FEE AUDITOR TERHADAP KUALITAS AUDIT (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2019)
This research was aimed to examine empirically the effect of audit independence, audit feeÂ and audit quality. The analysis used an independent variable of audit indpendence and audit fee. The dependent variable is audit quality. The sample of this research are auditors who worked on Kantor Akuntan Publik (KAP) Representative of South Jakarta. The sample was conducted by purposive sampling method. Collecting data was conducted by a questionnaire distributed directly to auditors as much 67 questionnaires. The statistical method used was multiplied analysis linear regression, with hypotheses testing of statistic t-tests and hypotheses testing of statistic f-tests. The result of this research showed that audit independence, audit feeÂ and audit quality.. Pressure obedience significantlysimultaneously or partially on audit quality at the Kantor Akuntan Publik (KAP) in the South Jakarta area.